Centro Cultural Etnobotánico Bavaria rehabilitación y reciclaje de edificaciones con énfasis patrimonial (2021)
This degree work is based on the study, research and implementation of the national industrial heritage, specifically that which is contained in the polygon of the Techo Industrial Complex. It is proposed as a line of strategy for the revitalization and rehabilitation of the city the recycling of buildings, as a central axis not only of the situation previously mentioned but also as a way to give a new life cycle to those buildings with a high potential for this purpose, outlining and defining intervention tactics that help the conservation of the collective memory of the city, the ecosystem and the immediate environment through the implementation of activities related to culture, ethnobotany contributing to the optimal development of these places disconnected from the dynamics of the city.